2021
DOI: 10.1016/j.hlc.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Is Extracorporeal Membrane Oxygenation the Standard Care for Acute Respiratory Distress Syndrome: A Systematic Review and Meta-Analysis

Abstract: Background Acute respiratory distress syndrome (ARDS) is a type of acute respiratory failure syndrome characterised by severe respiratory distress and stubborn hypoxaemia. Patients with ARDS have a prolonged hospital stay and high mortality rate. Over long-term follow-up, ARDS is found to be associated with a high incidence of long-term complications and decreased quality of life. Venovenous extracorporeal membrane oxygenation (vv-ECMO) has been widely used for the treatment of refractory ARDS. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Despite advances in medical technology, the mortality rate for severe acute respiratory distress syndrome (ARDS) remains high at around 40% [1]. In recent years, multiple studies, systematic reviews, and meta-analyses [2][3][4][5], including the study in this issue of Heart, Lung and Circulation published by Wang and colleagues [4], have indicated that treatment with veno-venous extracorporeal membrane oxygenation (VV-ECMO) may be associated with better outcomes in severe ARDS than conventional mechanical ventilation. Increasing evidence will likely lead to an increase in the use of VV-ECMO in the treatment of ARDS in the coming years [6].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Despite advances in medical technology, the mortality rate for severe acute respiratory distress syndrome (ARDS) remains high at around 40% [1]. In recent years, multiple studies, systematic reviews, and meta-analyses [2][3][4][5], including the study in this issue of Heart, Lung and Circulation published by Wang and colleagues [4], have indicated that treatment with veno-venous extracorporeal membrane oxygenation (VV-ECMO) may be associated with better outcomes in severe ARDS than conventional mechanical ventilation. Increasing evidence will likely lead to an increase in the use of VV-ECMO in the treatment of ARDS in the coming years [6].…”
mentioning
confidence: 99%
“…ARDS is an acute inflammatory lung injury resulting in widespread alveolar injury and hypoxaemia [4,7]. There is no gold standard to diagnose ARDS, and each ARDS case can have a multitude of causes [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations